Brazilian donkeys (Equus asinus) have a low exposure to Neospora spp. - Galvão,Cynthia Maria Morais de Queiroz (2015)
Donkeys (Equus asinus) are closely related to horses and are known to be infected by several equine pathogens. Neospora caninum and Neospora hughesi are protozoan parasites that infect horses, but they were not confirmed in donkeys up to this date. The aim of this study was to evaluate the exposure of donkeys (Equus asinus) to Neospora spp. using tachyzoites of N. caninum as antigen and employing two common serologic methods, IFAT and immunoblot. Sera from 500 donkeys were obtained from 30 municipalities in Bahia state and tested by IFAT. Two of 500 sera were positive for Neospora spp. by IFAT with antibody titers of 100, and recognized a 37kDa antigen in immunoblot. Approximately 22% of the samples showed strong apical reactions and/or incomplete fluorescence, what may cause confusion in the interpretation of IFAT. We concluded that Neospora spp. are possibly of minor importance for Brazilian donkeys. Future studies are necessary to prove that Neospora spp. can naturally infect donkeys.